Risk factors for wheezing in infants born in Cuba - Venero-Fernandez, S.J.; Suarez-Medina, R.; Mora-Faife, E.C.; Garcia-Garcia, G.; Valle-Infante, I.; Gomez-Marrero, L.; Abreu-Suarez, G.; Gonzalez-Valdez, J.; Dania Fabro-Ortiz, D.; Fundora-Hernandez, H.; Venn, A.; Britton, J.; et al. (Oxford University Press, 2013)
Background: Cuba is a unique country, and despite limited economic development, has an excellent health system. However, the prevalence of asthma symptoms in children in Havana, Cuba, is unusually high.